As transformações históricas e a dinâmica atual da paisagem na bacia hidrográfica do Ribeirão São Francisco - Noroeste do Paraná - Montina, Neiriele Bruschi (2006)
The currente research proposes to an analysis of the Ribeirão São Francisco drainage basin, studying the historical t ransformat ions and the actual dynamics of the landscape where is verified such the division in small propert ies, explored, general rules, by the owners and their families and oriented by a regional development plan conducted by Companhia de Terras Nor te do Paraná (CTNP), as the huge impact of the silt ing up given by the ant ropic handles not by physics potent iality, which results in different react ions of the basins units (such as high, average and drainage basin) diferents reacts